Challenges of nurses in assisting patients with hearing disabilities: a literature review (Research, Society and Development, 2020)
Nursing is the science and art of caring, it is the health care of an individual, family, and their community, so it must do the process of promotion, maintenance, recovery of health. Communication plays a very important role in the process of assisting the hearing impaired client, and the deaf client, as it is the first stage of interaction, understanding of the clients, and thus discovering their point of view, assessing their problems, and from from that start the sequence of diagnoses and interventions. This is a literature review survey of the literature, with a qualitative approach and descriptive character in order to describe the challenges of nurses in assisting patients with hearing loss. Searches were carried out in the database of the Virtual Health Library (VHL) - Bireme, between June and July 2020, in the databases: Latin American and Caribbean Literature in Health Science (LILACS), Nursing Databases ( BDENF), Electronic Scientific Online Library (SciELO). From this preliminary reading, 10 articles were selected that maintained coherence with the presented descriptors and with the objectives of the study. It can be concluded that the present study shows that higher education has gaps in the professional training of nurses with regard to communication. It is essential that all nursing professionals are aware and aware that they should always be in search of new knowledge and training on social inclusion in the health of the hearing impaired.